Care and maintenance of leather upholstered furniture with traditional leather conditioners - Mihajlovski Nikola; Konstantin Bahchevandjiev (Faculty of Design and Technologies of Furniture and Interior-Skopje, 2019)
The upholstery leather in the furniture is exposed to intensive wear conditions and dust. Periodic cleaning and maintenance is necessary in order to maintain its properties. In the period of use the leather loses its natural fats, absorbs salts then becomes hard and cracks. Care and maintenance of leather in the upholstered furniture is a system of activities such as prevention, cleaning and conditioning of the leather. All these activities are interconnected to maintain the quality of the leather. The main task of the care products and maintaining of leather is its adjustment to the conditions of use, removal of deformations that occurred during use and prepare for its further use. The aim of this paper is to review the method of maintenance of the leather in the upholstered furniture as well as to compare the classical care products with the commercial ones through a review of literary and experiential data. Commercial conditioners do not satisfy the needs for conditioning the leather properties over a long period of time. Traditional conditioners made from animal fat, oils and waxes such as tallow, lanolin, fish oil and beeswax enhance collagen fibrils, maintain elasticity, contribute to hydrophobicity and increase its organoleptic properties.
Keywords: upholstery leather, leather furniture maintenance system, traditional leather conditioners, animal fats and waxes